The "Religious Secularism" of Lebanon and the United States: A Discussion between Lebanon's Secular Debate and Madison's "Principles of Pluralism" (American Journal of Islam and Society, 2002)
Within the current discussions of Jslam and democracy, the issue of secularism has now become one of the most important themes. Throughout the nineteenth and twentieth centuries, the main premise put forward by Jslamic scholars in various forms has been that secularism is atheistic and, therefore, incompatible with £slam. This article investigates one Islamic debate on the issue of secularism in order to find the root elements of the Muslim argument. In looking at the 1976-77 secularism debate in Lebanon we argue that, like Lebanon, most Muslim scholars use the French Revolution and its Jacobist views as the standard for understanding secularism. Rather, the Lebanese context is better suited to the eighteenth-century American context and its development of a "religious secularism." The conclusion here is that Lebanon would be better off using eighteenth-century American rhetoric in its social political discourse for a vision of its own future, and that Musi im minority communities (primarily in the United States) can recover the issues involved in the American secular debates that saw secularism as "freedom for religion" in multicommunal states rather than the enemy of religion.